Pengembangan Jobsheet Berbasis Industri pada Mata Kuliah Praktik Instalasi Listrik Industri - Muhammad Sabri; Elfizon Elfizon (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
Industrial Electrical Installation Practice is a subject in the Department of Electrical Engineering, Padang State University that must be taken by students. In practical implementation, they still use the old Jobsheet and have not used industry-based jobsheets, so students don't know much about existing equipment in the industry. The availability of industry-based jobsheets makes it easy for students to apply practical learning to Industry and get to know the many equipments in the Industry. For this reason, this study aims to produce a valid and practical industry-based jobsheet. The research method used is the Research and Development method with the 4D Model. The research subject was a practical Jobsheet for students majoring in Electrical Engineering FT UNP, for the 2020/2021 academic year. Based on the research results, the validity of the industry-based Jobsheet from the validators (media expert validators and material experts) obtained an average valid category. Practicality Test with respondents Lecturer in the Industrial Electrical Installation Practice Course obtained an average with the very practical category. From the research data above, it can be concluded that the industrial-based Industrial Electrical Installation Practice jobsheet is valid and practical to use for Industrial Electrical Installation Practices lectures.